Phylogenetic relationships of the Amblyomma cajennense complex (Acari: Ixodidae) at mitogenomic resolution - Cotes Perdomo, Andrea P. (2023)
The genus Amblyomma is the third most diverse in the number of species within the Ixodidae, with practically half of its species distributed in the Americas, though there are also species occurring in Africa, Asia, and Australia. Within the genus, there are several species complexes with veterinary and public health importance. The Amblyomma cajennense complex, in the Americas, is represented by six species with a wide distribution, from Texas to northern Argentina. We combined two sequencing techniques to generate complete mitogenomes of species belonging to the Amblyomma cajennense complex: genome skimming and long-range PCRs sequencing methods. Thus, we generated seven new mitochondrial genomes for all species of the Amblyomma cajennense complex, except for Amblyomma interandinum. Genetic distances between the mitogenomes corroborate the clear differentiation between the five species of the Amblyomma cajennense complex. The phylogenetic relationships of these species had previously been evaluated by combining partial nuclear and mitochondrial genes and here these relationships are corroborated with a more robust framework of data, which demonstrates that the conjunction of mitochondrial and nuclear partial genes can resolve close relationships when entire genes or genomes are unavailable. The gene order, structure, composition, and length are stable across these mitogenomes, and they share the general characteristics of Metastriata. Future studies should increase the number of available mitogenomes for this genus, especially for those species from the Indo-Pacific region and Africa, by means of a better understanding of their relationships and evolutionary process.